Business Models for Circular Economy and Sustainable Development: the Case of Lease Transactions - Ion Ionașcu; Mihaela Ionașcu (Amfiteatru Economic)
The purpose of this paper is to discuss the features of leasing as a business model in the circular economy, which is presumed to support sustainable development by product recirculation and driving economic performance. In particular, this study highlights microeconomic benefits for listed Romanian companies, showing that adopting a "greener" business model, as in the case of leasing, does not penalize firms economically but it is a catalyst for increasing their performance, both in terms of accountancy-based measures (return on assets and return on sales), but also in terms of the subjective perceptions of investors and financial analysts operating on the capital market (proxied by Tobin’s Q and market to book value of equity). Based on 266 observations from companies listed on the Bucharest Stock Exchange (BSE) during 2013-2016, the study uses regression analysis to show that financial performance is higher for quoted Romanian companies that use leasing and renting and that performance is also directly associated with leasing intensity, i.e. the share of the value of the rights to use leased goods in the total value of property, plant and equipment.